Full Wave Simulations of Lower Hybrid Waves in Toroidal Geometry with Non-Maxwellian Electrons (Communications in Computational Physics, 2008)
Analysis of the propagation of waves in the lower hybrid range of frequencies in the past has been done using ray tracing and the WKB approximation. Advances in algorithms and the availability of massively parallel computer architectureshas permitted the solving of the Maxwell-Vlasov system for wave propagation directly[Wright et al., Phys. Plasmas (2004), 11, 2473-2479]. These simulations have shownthat the bridging of the spectral gap (the difference between the high injected phasevelocities and the slower phase velocity at which damping on electrons occurs) canbe explained by the diffraction effects captured in the full wave algorithm - an effectmissing in WKB based approaches. However, these full wave calculations were donewith a Maxwellian electron distribution and the presence of RF power induces quasilinear velocity space diffusion that causes distortions away from an Maxwellian. Withsufficient power, a flattened region or plateau is formed between the point of mostefficient damping on electrons at about 2-3 νthe and where collisional and quasilinear diffusion balance. To address this discrepancy and better model experiment, wehave implemented [Valeo et al., "Full-wave Simulations of LH wave propagation intoroidal plasma with non-Maxwellian electron distributions", 18th Topical Conferenceon Radio Frequency Power in Plasmas, AIP Conference Proceedings (2007)] a non-Maxwellian dielectric in our full wave solver. We will show how these effects modifythe electron absorption relative to what is found for a Maxwellian distribution.